2003
DOI: 10.1074/jbc.m211630200
|View full text |Cite
|
Sign up to set email alerts
|

Signal Recognition Particle (SRP)-mediated Targeting and Sec-dependent Translocation of an Extracellular Escherichia coli Protein

Abstract: Hemoglobin protease (Hbp) is a hemoglobin-degrading protein that is secreted by a human pathogenic Escherichia coli strain via the autotransporter mechanism. Little is known about the earliest steps in autotransporter secretion, i.e. the targeting to and translocation across the inner membrane. Here, we present evidence that Hbp interacts with the signal recognition particle (SRP) and the Sec-translocon early during biogenesis. Furthermore, Hbp requires a functional SRP targeting pathway and Sec-translocon for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
103
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 30 publications
7
103
0
Order By: Relevance
“…7) further supports the involvement of FlhF in the regulation of protein secretion, as already reported for P. putida (Pandza et al, 2000). FlhF is a member of the SRP-GTPase family (Carpenter et al, 1992;Pandza et al, 2000) and shows substantial homology with Ffh and FtsY, two proteins required for extracellular accumulation of proteins in E. coli and B. subtilis (Sijbrandi et al, 2003;Zanen et al, 2006). Similarly to flhF disruption in B. cereus, Ffh or FtsY depletion in B. subtilis determines an increased level of various extracellular proteins (Zanen et al, 2006).…”
Section: Discussionmentioning
confidence: 53%
“…7) further supports the involvement of FlhF in the regulation of protein secretion, as already reported for P. putida (Pandza et al, 2000). FlhF is a member of the SRP-GTPase family (Carpenter et al, 1992;Pandza et al, 2000) and shows substantial homology with Ffh and FtsY, two proteins required for extracellular accumulation of proteins in E. coli and B. subtilis (Sijbrandi et al, 2003;Zanen et al, 2006). Similarly to flhF disruption in B. cereus, Ffh or FtsY depletion in B. subtilis determines an increased level of various extracellular proteins (Zanen et al, 2006).…”
Section: Discussionmentioning
confidence: 53%
“…These signal peptides contain a ϳ25-amino acid segment that resembles typical signal peptides as well as a ϳ25-amino acid N-terminal extension of unknown function. Previous results indicate that one member of the SPATE family, Hbp, is targeted to the IM by SRP (34). To determine whether the basic residues found in SPATE signal peptides promote SRP recognition, we first replaced the native signal peptides of MBP and OmpA, two proteins that are normally targeted by SecB, with either the complete EspP signal peptide or a truncated version that lacks the N-terminal extension (⌬Esp).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, two papers have been published that could give some clues. In these papers, Sijbrandi et al (12) and Szabady et al (13) study another group of large outer membrane proteins, the autotransporters. A subset of autotransporters also contains unusually long signal sequences that are, in fact, similar in composition to those of the TonB-dependent transducers (Fig.…”
mentioning
confidence: 99%
“…1). Sijbrandi et al (12) showed that these long signal sequences interact with the Sec translocon and with the signal recognition particle. This means that these proteins are transported cotranslationally.…”
mentioning
confidence: 99%